Neuro-Marketing in Understanding Consumer Behavior: Systematic Literature Review - Shashi Kant; Fisseha Dejene Yadete (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2023)
Neuromarketing and its implicit and automated processes influence customer decision-making and expose any concealed understanding of consumer behavior. There is a rising interest in studying how consumers' brain responses affect their decision-making process because one of the most important questions in today's market is what motivates consumers to choose one product over another. Although neuromarketing positions itself as one of the key fields of research targeted at accomplishing this objective, it is still a young and rapidly evolving discipline. The study's research proposal was to examine how advertising influences consumers' purchasing decisions when shopping online. Examining the role of customers' gaze spots, fixation counts, heat maps, and emotions in reaction to stimuli or marketing efforts is another goal. The consumer provides the stimulus, and the advertising effort gauges the response. The authors used a systematic literature review of the latest studies. The inclusion and exclusion of scanned literature was conducted with the help of PRISMA. For checking the effect size of the used literature, authors employed the forest plot based on partial correlation. The publication bias of SLR was viewed through the funnel plot. Bibliometrics analysis and content analysis were conducted to support the strength of the reviewed literature.